Articulating the Ḥijāba: Cultural Patronage and Political Legitimacy in al-Andalus The ʿĀmirid Regency c. 970-1010 AD - Rosser-Owen, Mariam (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2022)
In Articulating the Ḥijāba, Mariam Rosser-Owen analyses for the first time the artistic and cultural patronage of the 'Amirid regents of the last Cordoban Umayyad caliph, Hisham II, a period rarely covered in the historiography of al-Andalus.; Readership: All interested in the history, literature, art, architecture and archaeology of medieval Islamic Iberia, relations with the Maghrib, the organisation of artistic workshops, and the patronage and meaning of artworks